Pemikiran Tokoh-Tokoh Ekonomi Islam Mengenai Konsep Penetapan Harga Pasar - Moh. Asep Zakariya Ansori; Abdul Aziz; Dicky Irmansyah; Irma Wati; Dinda Aulia Rahmi; Nadya Rahma Putri Latiepah; Muhammad Andri Ramadhan (Economic Reviews Journal, 2024)
This journal discusses the thoughts of Islamic economic figures regarding the concept of market price determination. The figures discussed include Ibn Taymiyyah, Al-Mawardi, Abu Yusuf, Al-Ghazali, and Ibnu Khaldun. The methodology used is literature study. The results show that according to these figures, prices should be determined by market mechanisms and the interaction between demand and supply. However, under certain conditions, for example market distortion, the government is allowed to intervene in price fixing to protect public interests. In conclusion, Islamic economic figures agree that basically prices must be determined by competitive market mechanisms, but government intervention is permitted under certain conditions to protect community interests and restore market balance.